2021
DOI: 10.1186/s12929-021-00774-y
|View full text |Cite
|
Sign up to set email alerts
|

Three decades of Cdk5

Abstract: Cdk5 is a proline-directed serine/threonine protein kinase that governs a variety of cellular processes in neurons, the dysregulation of which compromises normal brain function. The mechanisms underlying the modulation of Cdk5, its modes of action, and its effects on the nervous system have been a great focus in the field for nearly three decades. In this review, we provide an overview of the discovery and regulation of Cdk5, highlighting recent findings revealing its role in neuronal/synaptic functions, circa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
66
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(67 citation statements)
references
References 190 publications
0
66
0
1
Order By: Relevance
“…Myristoylatation of the p35/39 helps to associate Cdk5 to vesicles and plasma membrane. Calpain-dependent proteolysis of p35 at the plasma membrane hyperactivates the enzyme (Pao and Tsai, 2021). The enzyme targets a large variety of proteins involved in multiple different pathways (Gao et al, 2021).…”
Section: Phosphoregulation Of Kinesin-3mentioning
confidence: 99%
“…Myristoylatation of the p35/39 helps to associate Cdk5 to vesicles and plasma membrane. Calpain-dependent proteolysis of p35 at the plasma membrane hyperactivates the enzyme (Pao and Tsai, 2021). The enzyme targets a large variety of proteins involved in multiple different pathways (Gao et al, 2021).…”
Section: Phosphoregulation Of Kinesin-3mentioning
confidence: 99%
“…The kinases displaying the lowest false-discovery rate across the dataset using Fisher’s Exact test were: Atm/Atr, Prkdc (DNA-PKcs), Gsk3-Erk1-2, Cdk5-Cdk and Cdc2b (Fig. 3C); kinases respectively belonging to the DDR, stem cell potency, and cell cycle control (Blackford and Jackson, 2017; Pao and Tsai, 2021; Singh et al, 2012). We note that Gsk3-Erk1-2 phosphorylation differences were expected given the maintenance of primed and naïve stem cell states requires culture modulation of FGF, activin, and LIF, which signal through Gsk3-Erk1-2 pathways (Cho et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…Studies have revealed that neuroprotection is correlated with the inhibition of neuron-specific CDK5 [64]. For neurite outgrowth and cortical lamination, CDK5 and its neuron-specific activator p35 are essential [65]. Proteolytic cleavage of CDK 5 activator p35 by calpain led to the formation and accumulation of p25 in the brain of AD patients [66].…”
Section: Phyto-carbazole Alkaloids From the Genus Clausenamentioning
confidence: 99%